1995
DOI: 10.1152/ajprenal.1995.268.6.f1211
|View full text |Cite
|
Sign up to set email alerts
|

HGF-mediated chemotaxis and tubulogenesis require activation of the phosphatidylinositol 3-kinase

Abstract: The association of hepatocyte growth factor (HGF) with its high-affinity receptor, c-met, has been shown to induce mitogenesis, motogenesis, and morphogenesis in renal epithelial cells (L. G. Cantley, E. J. G. Barros, M. Gandhi, M. Rauchman, and S. K. Nigam. Am. J. Physiol. 267 (Renal Fluid Electrolyte Physiol. 36): F271-F280, 1994), suggesting that HGF may be critical to the orchestration of both renal development and regeneration following injury. Although signal transduction pathways activated by c-met incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 0 publications
6
71
1
Order By: Relevance
“…1, UB cells were cytokeratin-positive, Ecadherin-positive, ZO-1-positive, and partially (5-30%, depending on passage) vimentin-positive, consistent with an epithelial character as previously described (25). In contrast, BSN cells (passage [4][5][6][7][8][9][10][11][12][13][14] were negative for cytokeratin, though strongly positive for vimentin, consistent with a mesenchymal character. No cell surface staining for E-cadherin or ZO-1 was observed, though some faint cytoplasmic staining of ZO-1, which has been reported for a number of mesenchymal cell lines (31), was observed.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…1, UB cells were cytokeratin-positive, Ecadherin-positive, ZO-1-positive, and partially (5-30%, depending on passage) vimentin-positive, consistent with an epithelial character as previously described (25). In contrast, BSN cells (passage [4][5][6][7][8][9][10][11][12][13][14] were negative for cytokeratin, though strongly positive for vimentin, consistent with a mesenchymal character. No cell surface staining for E-cadherin or ZO-1 was observed, though some faint cytoplasmic staining of ZO-1, which has been reported for a number of mesenchymal cell lines (31), was observed.…”
Section: Resultssupporting
confidence: 74%
“…Systems for branching tubulogenesis that have been employed previously utilize cell lines such as MDCK or mIMCD3 derived from the mature kidney (10)(11)(12)(13)(14)(15)(16)36). In these cell lines, the major factors capable of inducing early cellular process formation leading to branching tubulogenesis appear to be HGF and EGFR ligands (e.g., EGF, TGF-␣, heparin-binding EGF, amphiregulin, betacellulin) (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, phosphorylation of Gab1 by HGF receptor may allow Gab1 to bind to SHP2 and/or PI3K, which then contributes to HGFinduced cell motility (Figure 9b). Accordingly, Crk has been shown to enhance HGF-induced mitogenesis (Riordan et al, 2000), whereas PI3K has been shown to be important for HGF-induced chemotaxis (Derman et al, 1995;Machide et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, various factors have been discovered to be involved in branching tubulogenesis. Murine inner medullary collecting duct (IMCD)-3 cells (1,5,7,26) or rat primary tubular cells (4) are also utilized for the study of tubulogenesis. These in vitro models, in which HGF has been shown to induce tubular formation, are well defined, practical, and contribute to an understanding of the mechanism of tubulogenesis.…”
mentioning
confidence: 99%